1999
DOI: 10.1105/tpc.11.8.1433
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the anthocyanin2 Gene of Petunia and Its Role in the Evolution of Flower Color

Abstract: The shape and color of flowers are important for plant reproduction because they attract pollinators such as insects and birds. Therefore, it is thought that alterations in these traits may result in the attraction of different pollinators, genetic isolation, and ultimately, (sympatric) speciation. Petunia integrifolia and P. axillaris bear flowers with different shapes and colors that appear to be visited by different insects. The anthocyanin2 ( an2 ) locus, a regulator of the anthocyanin biosynthetic pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
306
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(319 citation statements)
references
References 50 publications
12
306
0
1
Order By: Relevance
“…This QTL corresponds to the gene F3 0 5 0 h. Wessinger & Rausher [13] demonstrated using co-segregation and functional analyses that this gene is redundantly non-functional in P. barbatus and completely explains the difference in flower colour between the two species. Similar large effect flower colour QTLs have been reported frequently for adaptation to different pollinators between pairs of species within Aquilegia [35], Ipomopsis [15], Iris [14,17], Iochroma [36], Mimulus [9,37] and Petunia [10,18]. One partial explanation for this pattern is that many flower colour transitions involve deactivation of parts or all of the anthocyanin pathway, which can be accomplished by inactivating mutations in one or a few genes [10,13,36 -38].…”
Section: Discussion (A) Genetic Basis Of Pollination Syndrome Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…This QTL corresponds to the gene F3 0 5 0 h. Wessinger & Rausher [13] demonstrated using co-segregation and functional analyses that this gene is redundantly non-functional in P. barbatus and completely explains the difference in flower colour between the two species. Similar large effect flower colour QTLs have been reported frequently for adaptation to different pollinators between pairs of species within Aquilegia [35], Ipomopsis [15], Iris [14,17], Iochroma [36], Mimulus [9,37] and Petunia [10,18]. One partial explanation for this pattern is that many flower colour transitions involve deactivation of parts or all of the anthocyanin pathway, which can be accomplished by inactivating mutations in one or a few genes [10,13,36 -38].…”
Section: Discussion (A) Genetic Basis Of Pollination Syndrome Traitsmentioning
confidence: 99%
“…Yet, some empirical evidence from quantitative trait locus (QTL) studies on pollination syndrome divergence suggests that there may be common patterns at the genetic level. For example, previous QTL studies have suggested that traits such as flower colour and nectar volume often involve few substitutions of medium to large effect [9][10][11][12][13], while changes in morphological characters tend to involve more loci with smaller effects [12,14,15]. In addition, these studies have revealed that QTLs for different traits sometimes co-localize (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The shape and colour of flowers are important for plant sexual reproduction (Quattrocchio et al 1999). Flowers of diverse species display a wide range of different morphologies and pollination strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Flowers of diverse species display a wide range of different morphologies and pollination strategies. For instance, windpollinated plants have small petals and inconspicuous colours or no petals at all, whereas animal-pollinated plants have developed display structures often characterized by brightly coloured and patterned petals that serve as visual signals and a landing site for visiting insects (Menzel and Shmida 1993;Quattrocchio et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, natural plant populations often and persistently harbor rare fl ower color morphs that frequently include white morphs caused by mutations in biosynthetic pathways for fl oral pigments ( Quattrocchio et al, 1999 ;Schwinn et al, 2006 ;Streisfeld and Rausher, 2009 ). The most widely distributed fl oral pigments are anthocyanins that provide red to blue color to petals and are produced from the highly conserved fl avonoid biosynthetic pathway (reviewed in Grotewold, 2006 ).…”
mentioning
confidence: 99%